Social capital in transition(s) to early adulthood: a longitudinal and mixed-methods approach - Neves, B. B.; De Carvalho, D. D.; Serra, F.; Torres, A.; Fraga, S. (Journal of Adolescent Research, 2019)
Social capital captures the value of relationships. Although research has examined social capital among adults, comparatively little attention has been paid to social capital among young adults—particularly from a longitudinal and mixed-methods perspective. As social capital predicts educational achievement, employment, and psychosocial well-being, it is an important construct to study alongside youth transition(s). Following a Bourdieusian approach, we define social capital as the resources potentially available in our ties that can be mobilized when necessary. To examine social capital in transition to adulthood, we draw on survey (n = 1,650, at ages 17 and 21) and interview (n = 70, at age 24) data from a cohort of Portuguese youth. We study the two main dimensions of social capital: bonding and bridging. Survey data were analyzed with latent class modeling, logistic regressions, and Wilcoxon signed-rank tests, and interviews with thematic analysis. Findings show that respondents reported receiving more emotional support than financial support from their networks, but that both types of support increased over time. Perceived bonding and bridging also changed positively in transition to adulthood. In addition, gender and parental education predicted bonding and bridging. We contextualize these results with qualitative meanings and experiences of social capital.